1987
DOI: 10.1056/nejm198712173172503
|View full text |Cite
|
Sign up to set email alerts
|

Splenic Reticuloendothelial Function after Splenectomy, Spleen Repair, and Spleen Autotransplantation

Abstract: Overwhelming infection after splenectomy remains a problem despite the introduction of vaccine and antimicrobial prophylaxis. To evaluate prospectively various procedures proposed for salvage of the spleen, we measured reticuloendothelial function for two to five years in 51 patients who had initially presented with abdominal trauma and suspected splenic rupture. The mean percentage of pocked erythrocytes and the clearance of antibody-coated autologous erythrocytes in 8 patients who had splenic repair and in 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
51
0
13

Year Published

1987
1987
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(67 citation statements)
references
References 35 publications
2
51
0
13
Order By: Relevance
“…However, total removal of the spleen may lead to side effects such as postsplenectomy infections and sepsis, due to the decreased production of antibodies and phagocytes or thrombosis, due to elevated platelet count in blood (Bessler et al, 2004;Khan et al, 2009;Miko et al, 2003;Timens & Leemans, 1992). Also, many studies report increased count of morphologically abnormal erythrocytes, immature red blood cells and pathologic erythrocyte inclusions in the peripheral blood of various species following splenectomy as a result of the loss of splenic filtrating function (Haklar et al, 1997;Resende et al, 2002;Traub et al, 1987). In addition, it has been reported that removal of the spleen causes significantly higher increase of reticulocyte count than other surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…However, total removal of the spleen may lead to side effects such as postsplenectomy infections and sepsis, due to the decreased production of antibodies and phagocytes or thrombosis, due to elevated platelet count in blood (Bessler et al, 2004;Khan et al, 2009;Miko et al, 2003;Timens & Leemans, 1992). Also, many studies report increased count of morphologically abnormal erythrocytes, immature red blood cells and pathologic erythrocyte inclusions in the peripheral blood of various species following splenectomy as a result of the loss of splenic filtrating function (Haklar et al, 1997;Resende et al, 2002;Traub et al, 1987). In addition, it has been reported that removal of the spleen causes significantly higher increase of reticulocyte count than other surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…So, autotransplantation or the preservation of splenenculi after total splenectomy has been practiced to prevent post splenectomy sepsis. [11][12] Total splenectomy has been practiced for a long time for palliation for thalassemic children. Conceivably it provides the best opportunity for palliation in thalassemic children by removing a substantial portion of reticuloendothelial system.…”
Section: Introductionmentioning
confidence: 99%
“…For protection against infection, an intact spleen is better than a repaired or autotransplanted spleen, 93 while an accessory spleen and splenosis seem to be only slightly better than asplenia. Surgical or interventional radiologic techniques should be employed to maximize residual splenic tissues in cases of splenic injury.…”
mentioning
confidence: 98%
“…Traub et al 93 studied splenic reticuloendothelial function after splenectomy, spleen repair and spleen autotransplantation. They showed that partial splenectomy and splenic repair were better than splenic autotransplantation in protecting against OPSI.…”
mentioning
confidence: 99%